The effect of estrogenic compounds on psychosis-like behaviour in female rats. - Alyssa Sbisa; Maarten van den Buuse; Andrea Gogos (PLoS ONE, 2018)
17β-estradiol treatment has shown benefit against schizophrenia symptoms, however long-term use may be associated with negative side-effects. Selective estrogen receptor modulators, such as raloxifene and tamoxifen, have been proposed as suitable alternatives to 17β-estradiol. An isomer of 17β-estradiol, 17α-estradiol, is considered less carcinogenic, and non-feminising in males, however little is known about its potential as a treatment for schizophrenia. Moreover, the mechanism underlying the therapeutic action of estrogens remains unclear. We aimed to investigate the ability of these estrogenic compounds to attenuate psychosis-like behaviour in rats. We used two acute pharmacologically-induced assays of psychosis-like behaviour: psychotomimetic drug-induced hyperlocomotion and disruption of prepulse inhibition (PPI). Female Long Evans rats were either intact, ovariectomised (OVX), or OVX and chronically treated with 17β-estradiol, 17α-estradiol, raloxifene or tamoxifen. Only 17β-estradiol treatment attenuated locomotor hyperactivity induced by the indirect dopamine receptor agonist, methamphetamine. 17β-estradiol- and tamoxifen-treated rats showed attenuated methamphetamine- and apomorphine (dopamine D1/D2 receptor agonist)-induced disruption of PPI. Raloxifene-treated rats showed attenuated apomorphine-induced PPI disruption only. Baseline PPI was significantly reduced following OVX, and this deficit was reversed by all estrogenic compounds. Further, PPI in OVX rats was increased following administration of apomorphine. This study confirms a protective effect of 17β-estradiol in two established animal models of psychosis, while tamoxifen showed beneficial effects against PPI disruption. In contrast, 17α-estradiol and raloxifene showed little effect on dopamine receptor-mediated psychosis-like behaviours. This study highlights the utility of some estrogenic compounds to attenuate psychosis-like behaviour in rats, supporting the notion that estrogens have therapeutic potential for psychotic disorders.